Assessment of Iodine Deficiency among School-Going Children of Age Group 6 to 12 Years in Kachchh District, Gujarat State: Cross-Sectional Hospital-Based Study - Sharma, Dinesh P.; Maheshwari, Amitkumar; Chakrabarti, Chandan; Patel, Darshan J. (Journal of Laboratory Physicians, 2021)
Aim Iodine deficiency disorder (IDD) is the cause of preventable brain damage, mental retardation, and stunted growth and development in children. This study aimed to detect the prevalence of IDD in Kachchh district, Gujarat, by testing urinary iodine excretion levels and iodine intake of salts in school-going children.Methods A cross-sectional study was conducted and the level of iodine deficiency was assessed in 223 school children of both sexes, aged 6 to 12 years from four talukas, that is, subdivisions, of the Kachchh district by estimating urinary iodine using Sandell–Kolthoff reaction along with iodine content in edible salt samples by MBI kit (STK-Spot testing kit, MBI Kits International, Chennai, TN, India).Results The median urinary iodine level was found to be 194 μg/L, indicating no biochemical iodine deficiency in the region. In the study areas, 1% of the population showed a level of urinary iodine excretion < 50 μg/L. About 83% salt samples had iodine level more than 15 ppm and the iodine content in salt samples less than 15 ppm was only about 17%, indicating the salt samples at households contain iodine in adequate level.Conclusion There is a need of periodic surveys to assess the change in magnitude of IDD with respect to impact of iodized salt intervention.Furthermore, to strengthen National Iodine Deficiency Disorders Control Program, factors should be identified. There is also a need to prevent and reimpose the ban on the sale of noniodized salts in Gujarat.
Keywords: iodine deficiency disorders (IDD); school children; prevalence of goitre; iodized salts; urine iodine excretion